Development in Difficult Times: Russia's Arctic Policy Through 2035 - Aliyev, Nurlan (DEU, 2024)
Russia's new Arctic strategy lays out plans for the region through 2035. While the main threats to the region are social and economic, Moscow currently prioritizes increased military spending. Moscow's dilemma of whether to open up for increased economic investment, including from foreign companies, or remain closed to pursue its vision of national sovereignty will shape Arctic developments for years to come.